AUTOMATED BLOOM’S TAXONOMY-BASED QUESTION GENERATION FOR COURSE OUTCOME ATTAINMENT IN OBE FRAMEWORKS - Paul P, Blessy; Kurian, Cini; T Abraham, John (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The creation of assessment questions that align with Bloom’s taxonomy levels and achieve Course Outcomes (COs) is a critical yet complex task in Outcome-Based Education (OBE). Traditional manual methods, reliant on subject experts, are time-consuming and prone to gaps in addressing all COs or Bloom’s levels. While Large Language Models (LLMs) like ChatGPT can generate questions, they lack access to private data, including prescribed textbooks and syllabi, potentially leading to questions beyond the scope of the curriculum. This paper presents a novel system leveraging Retrieval-Augmented Generation (RAG) to automate the generation of Bloom’s taxonomy-based questions within the syllabus scope, ensuring comprehensive CO attainment. The proposed system integrates a vector database to store private data, including scanned textbooks, syllabi, Bloom’s taxonomy levels, and COs. The RAG model, trained on this curated dataset, generates questions that fulfill the cognitive, psychomotor, and affective domain requirements specified in the syllabus. This approach not only ensures alignment with educational objectives but also significantly reduces the manual effort involved in question preparation. The system’s efficacy is demonstrated through its ability to produce high-quality, targeted questions that effectively support OBE evaluation and enhance educational quality. This innovation addresses a critical gap in automated question generation for modern education systems.